Keterlibatan perempuan dalam konservasi satwa melalui kegiatan penangkaran burung - Nurul Marufi; Burhanudin Masy'ud; Arzyana Sunkar (Graduate School Bogor Agricultural University (SPs IPB), 2019)
The nature of caring and nurturing that shown by women makes them tend to care about the wildlife.Women are able to play a role in the captivity birds because related to household activity of caring. The study aims to identify the profile of the captive breeding and the women who are involved. The data obtained from 90 respondent by interview and observation. The respondents, which are the captive breeding in the area of Bogor and Klaten that accommodate protected species of birds, were determined by using a purposive sampling method. Based on the result, both captive breedings in Klaten and Bogor have involved women in the middle scale as well as in the household scale. Most women who are involved in the activities of captive breeding of the birds are in the age between 31 and 40 years with high school degree as their highest educational background and married women. In Bogor and the middle scale of captive breeding in Klaten, economic improvement is the sole motivation that has driven the women to be involved in the captive breeding activities. While, in the household scale in Klaten there are two motivations, which are economy and spare time.